The Correlation of Leg Length, Jump Height, and Leg Muscle Explosive Power Toward Sprint Ability - Ananda Perwira Bakti; Nining Widyah Kusnanik; Endang Sri Wahjuni; Awang Firmansyah; Indra Himawan Susanto; Lutfhi Abdil Khuddus (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The study purpose was to investigate the relationship between sprint ability at elementary school and leg length, jump height and leg explosive power. Sports coaching starting at the school level, where students are led and trained to have a strong, skilled, nimble, and agile mentality, athletic is very appropriate. One factor, specifically leg length (anatomy), jump height, and leg explosive power (physiology) in sprinting, affects an athlete's performance. The method Cross-sectional quantitative descriptive research is the method used in this study. A total of 61 male students between the ages of 10 and 12 made up the research sample. Measurements of leg length, jump height, leg explosive power, and a 40-meter sprint are used to obtain data. The normality test, correlation test, and table presentation were used in the descriptive data analysis. The results The results stated that the average leg length was 83.46 ± 5.43 cm, the average jump height was 17.91 ± 5.52 cm, the average explosive power of leg was 1451.61 ± 399.45 watts, and the average speed was 8.70 ± 1.61 m/s. If the calculated r value is less than the r table value, then there is a very weak correlation between the leg length variable and the speed variable. The results of the correlation test between leg length and speed obtained r count 0.137 and r table 0.254. There is a weak correlation between the leg explosive power variable and the speed variable, is evidenced by the correlation test results between leg power and speed, which were r count -0.369 and r table 0.254. There is a strong correlation between the jump height variable and the speed variable, as evidenced by the correlation value test results between the jump height value and the speed value, which show a correlation coefficient value of -0.715 and a sig value of 0.000, which is smaller than 0.05. According to the study's findings, sprint students at elementary school have a correlation between leg length, leg muscle explosive power, and jump height.